2001
DOI: 10.1146/annurev.pharmtox.41.1.661
|View full text |Cite
|
Sign up to set email alerts
|

Prostanoid Receptors: Subtypes and Signaling

Abstract: Cyclooxygenases metabolize arachidonate to five primary prostanoids: PGE(2), PGF(2 alpha), PGI(2), TxA(2), and PGD(2). These autacrine lipid mediators interact with specific members of a family of distinct G-protein-coupled prostanoid receptors, designated EP, FP, IP, TP, and DP, respectively. Each of these receptors has been cloned, expressed, and characterized. This family of eight prostanoid receptor complementary DNAs encodes seven transmembrane proteins which are typical of G-protein-coupled receptors and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
894
1
8

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 919 publications
(922 citation statements)
references
References 139 publications
14
894
1
8
Order By: Relevance
“…Therefore, COX-1 is involved in the synthesis of constricting prostanoids. Prostanoids act on smooth muscle via prostanoid receptors [26]. YC-1 induced constrictions were completely abolished by the TP receptor antagonist SQ 29,548, further corroborating the notion that vasoconstrictor prostanoid release is essential.…”
Section: Commentsupporting
confidence: 63%
See 1 more Smart Citation
“…Therefore, COX-1 is involved in the synthesis of constricting prostanoids. Prostanoids act on smooth muscle via prostanoid receptors [26]. YC-1 induced constrictions were completely abolished by the TP receptor antagonist SQ 29,548, further corroborating the notion that vasoconstrictor prostanoid release is essential.…”
Section: Commentsupporting
confidence: 63%
“…COX-derived prostanoids constitute a major part of EDCF [37]. Prostanoids act on smooth muscle via prostanoid receptors [26]. TP receptors have been shown to mediate vasoconstrictions by ET-1 in spontaneously hypertensive rats but not in normotensive control animals [38].…”
Section: Commentmentioning
confidence: 99%
“…Recent reports demonstrate species-specific splice variants of prostanoid receptors and differential activation of prostanoid receptors in various cell types and organs. For example, at least eight EP3 receptor splice variants have been identified in humans [15,16]. Thus, a diversity of prostanoid receptor expression and differential activation upon various stimuli may explain complexity of responses to prostaglandin stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PGI 2 -mediated activation of PPAR beta/delta and gamma and PGE 2 -dependent PPAR delta activation has been reported [14,15]. All type of these receptors are expressed in endothelium [14], and both EP and IP receptors are expressed in lung tissue [16]. Gq-coupled EP1 belongs to "contractile" group of prostanoid receptors and activates PLC, leading to intracellular calcium increase.…”
Section: Introductionmentioning
confidence: 99%
“…18 Interestingly, iPF2αIII can bind to and activate the thromboxane A2-prostanoid (TP) receptor, a G-protein coupled receptor with two alternatively spliced isoforms (α and β) that demonstrate similar pharmacological properties. 19,20 The TP receptor is present on platelets and several other cell types, including neurons and glia within the mammalian brain, 20,21 and a recent study demonstrated that TP receptor activation by iPF2αIII elevates APP protein expression and consequently Aβ peptide levels through stabilization of APP mRNA. 22 These data thus suggest that formation of iPF2α during AD progression may further contribute to disease pathogenesis through pathways leading to increased Aβ deposition, and that inhibition of TP receptor activation by iPF2αIII may be an important unexplored therapeutic strategy to lower Aβ levels in AD.…”
mentioning
confidence: 99%